METAPHOR AS A CRITERION OF MENTALITY (ON THE MATERIALS OF KARAKALPAK AND ENGLISH WRITERS WORKS) - Karjawbaev Orazali Esbosin uli (Western European Studies, 2024)
If we want to understand how metaphors might have a functional role in generating new hypothesis we should be aware of three things. First we should notice the difference between a metaphor and its related metaphorical utterances. Second we should be aware that metaphors are always untrue. Lastly we should distinguish metaphors from analogy or simile, mainly because analogies usually are true. The article deals with the study of Linguacultural analysis of metaphors in the works of English and Karakalpak writers — metaphor in the poetic works of the famous Karakalpak poet-classic of the XIX-th century Ajiniyaz. Individual genuine metaphors are of a great importance, because they are coined by the poet and show the peculiarities of the individual style of the poet.
Keywords: metaphor; language metaphor; figurative metaphor